(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2016)
The essay analyzes the results of an empirical research on preventive measures imposed by the Court of Milan in the last fifteen years (2000-2015) on persons suspected of being members of Mafia-type organizations. Alongside quantitative aspects, it has been carried out a qualitative analysis of confiscation measures against organized crime, through a study of the most significant cases. Keywords: preventive measures; confiscation; organized crime